1986
DOI: 10.1161/01.cir.74.6.1266
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of myocardial infarct structure in patients with ventricular tachycardia.

Abstract: To study whether myocardial infarction differs in patients with and without ventricular tachycardia, the hearts of 22 deceased patients with ventricular tachycardia and 21 deceased control patients were analyzed quantitatively. The hearts from the ventricular tachycardia group were heavier and more dilated than those from the control group. Histologic analysis of a representative cross section from each heart showed that the ventricular tachycardia group had larger, more solid infarcts than did the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 38 publications
5
44
0
Order By: Relevance
“…Table 2 lists the univariable predictors of mortality with PϽ0. 10. When all of the clinical and imaging parameters associated with mortality on univariable analysis were considered in the multivariable model by stepwise forward selection, %MDE periphery and LV end-systolic volume index emerged as the 2 strongest independent predictors of allcause mortality (Table 2) and cardiovascular mortality.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Table 2 lists the univariable predictors of mortality with PϽ0. 10. When all of the clinical and imaging parameters associated with mortality on univariable analysis were considered in the multivariable model by stepwise forward selection, %MDE periphery and LV end-systolic volume index emerged as the 2 strongest independent predictors of allcause mortality (Table 2) and cardiovascular mortality.…”
Section: Resultsmentioning
confidence: 97%
“…5,6 Although dense, fibrous scars in the infarcted myocardium incapable of depolarization cannot alone cause arrhythmias, when surrounded by distorted bundles of surviving myocytes capable of depolarization in the infarct border zone, arrhythmogenic substrates for slow conduction and reentry phenomena may arise. [7][8][9][10][11][12][13] …”
mentioning
confidence: 99%
“…Slow conduction, a required component of reentrant arrhythmias, is found in the border of healing infarcts [33,34]. In addition, areas of patchy infarct that may provide the geometric substrate for reentry [15], as well as areas of mixed dead and viable myocardium [21] have all been identified in the peri-infarct zone.…”
Section: Discussionmentioning
confidence: 99%
“…Infarct size is a known determinant of the risk for occurrence of VT [15][16][17]. Recent human studies have demonstrated that infarct characterization by late gadolinium enhancement (LGE) on CMR is predictive of overall mortality [12] as well as inducibility of ventricular arrhythmia during electrophysiological study (EPS) [11,18].…”
Section: Introductionmentioning
confidence: 99%
“…1 Sustained MVT typically occurs in the chronic phase after MI and is associated with left ventricular dysfunction and scarring. 2, 3 The risk of sudden cardiac death (SCD) from sustained MVT depends on the hemodynamic tolerance of the arrhythmia. Faster MVTs are typically less tolerated and more likely to lead to hemodynamic collapse and cardiac arrest.…”
Section: Risk Stratification For Ventricularmentioning
confidence: 99%